Interactive Animation Based Learning Media on Starter System Materials for Vocational Students - Arif Priambodo; Zainal Arifin (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
This study aimed at (1) developing interactive animated learning media on starter system materials for the subject of light electrical vehicle maintenance, (2) examining the effectiveness of developed media assessed from the aspects of display, program, and interactive based on students’ responses. The research model used was the development model of Analysis, Design, Development, Implementation, and Evaluation (ADDIE) developed by Branch. This study was conducted at SMK PGRI 4 Ngawi. Instruments used to obtain data were interviews and questionnaires. Product development was validated by material experts and media experts, then was tested in small (limited) and large trials (field). The results of this development study were as follows: (1) The analysis result of developed media showed that the media is feasible to be used in learning or in a good category. (2) The results of the assessment showed that the aspects of display, program and interactivity were all in the good category.